New beaded lacewings (Insecta: Neuroptera: Berothidae) from Indochina - Li, Di; Aspöck, Horst; Aspöck, Ulrike; Liu, Xingyue (Zootaxa, 2020)
The family Berothidae (beaded lacewings) is poorly known from the Indochina Peninsula. Previously, three genera, Berotha Walker, 1860, Isoscelipteron Costa, 1863, and Lekrugeria Navás, 1929, and four species were recorded from Myanmar, Thailand, and Vietnam. Here, we record the genus Asadeteva U. Aspöck & H. Aspöck, 1981, in Indochina for the first time and provide a description of a new species, namely Asadeteva acutata sp. nov., from Laos and Thailand. We also describe a new species of the genus Berotha Walker, 1860, namely Berotha incurvata sp. nov. from Laos and provide the first description of the male of Lekrugeria nepalica U. Aspöck & H. Aspöck, 1986, based on material from northern Myanmar.